(untitled) (Research, Society and Development, 2020)
This article aimed to identify the percentage of growth of teachers with higher education in elementary education in public and private schools, comparing them and their possible causes. To this end, we sought to: historically identify the evolution of the treatment given to public basic education; realize that the educational phenomenon that occurred in the 1990s led to the change that enabled the growth of teachers in elementary education in the public system; and observe which educational guidelines were applied for the growth of teachers with higher education in public schools and their equivalence with private schools. The methodology used was bibliographic research and the period analyzed was from 1999 to 2006. It is concluded that the determining factors in the increase of teachers with higher education in elementary education in Amazonas was the creation of new degree courses and agreements signed between city halls and universities to graduate lay teachers from their teaching staff.